Thought Control Ability Is Different from Rumination in Explaining the Association between Neuroticism and Depression: A Three-Study Replication - Lu, Feng-Ying; Yang, Wen-Jing; Zhang, Qing-Lin; Qiu, Jiang (Frontiers in Psychology, 2017)
Neuroticism is the most common vulnerability factor of depression. However, the mechanism underlying this vulnerability is still unclear. Previous studies suggested that rumination intensifies the negative effect of neuroticism on depression. However, whether cognitive control could explain the association between neuroticism and depression remains unclear to date. Therefore, this study evaluated the indirect effects of rumination and thought control on the relationship between neuroticism and depression. Seven self-report measures were employed among healthy and main depression disorder (MDD) participants. Three studies were used to examine the hypotheses. Results of the three studies showed significant correlations among neuroticism, rumination, thought control, and depression. Rumination mediated the link between neuroticism and depression among healthy young adults, and this finding replicated previous studies. This study provided new evidence that thought control mediates the association between neuroticism and depression in both healthy and MDD populations. In conclusion, rumination increases neuroticism risk for depression, but high-level thought control decreases the effect of neuroticism on depression. This study may serve as a reference to develop effective and focused interventions for MDD patients.